Exploring implementation of the Careful Nursing Philosophy and Professional Practice Model© in hospital‐based practice. (19th October 2017) - Murphy, Sinéad; Mc Mullin, Raphael; Brennan, Sinéad; Meehan, Therese Connell
Abstract : Aim: To explore the effectiveness and feasibility of implementing the two clinical dimensions of the Careful Nursing Philosophy and Professional Practice Model © (Careful Nursing) in an acute care hospital. Background: Implementation of a professional practice model by nurses in hospitals supports nurses' control over their practice and enhances the quality of their contribution to patient care. Implementing such change is complex and initially best approached on a small scale. Methods: A mixed methods exploratory design was used. Data were sought from 23 professional nurses practising in a 26‐bed acute medical ward for older persons. Quantitative data were collected on nurses' control over and documentation of their practice. Qualitative data were collected on nurses' perceptions of their practice. Result: Nurses' control over practice and adherence to practice documentation standards increased. Overall, the nurses perceived Careful Nursing‐guided practice positively. Feasibility issues were identified and addressed. Conclusion: Exploratory evidence suggests that Careful Nursing could influence nurses' practice and overall perception of practice positively; its implementation is feasible. Implications for Nursing Management: Careful Nursing offers a distinctive nursing framework for professional practice. This study can provide a strategy for implementing Careful Nursing‐guided changes in hospital‐based practice on an exploratory level.